Memoirs of Vaidyas The Lives and Practices of Traditional Medical Doctors in Kerala, India (1) - TSUTOMU YAMASHITA P. RAM MANOHAR (eJournal of Indian Medicine Volume 1 (2007-2008), 43-60, 2007)
This article presents an English translation of interview with a doctor of traditional poison- therapy (vi.avaidya), V*** S*** Namp.tiri (1917~ ) in Kerala, India. The contents of the interview are 1. Background and pre-sent circumstances, 2. Textual traditions, 3. Traditional medicines, 4. Treatments, 5. Mantra and reading omens and 6. The canon of vi.avaidya